Engineering Method for Calculating of an Axial Valve Separator With an External Location of the Locking Part - Kapranova, Anna; Neklyudov, Sergey; Lebedev, Anton; Meltser, Alexander; Voronin, Dmitriy (Frontiers in Energy Research, 2020)
The purpose of the work is to develop an analytical method for calculating the effective ranges of structural parameters of the throttle part of the axial valve with the external location of the locking shell based on the proposed stochastic models of bubble formation at the initial stage of hydrodynamic cavitation. In contrast to the well-known engineering methods for choosing the conditional bore diameter for the designed control device constructed using the Pi-Buckingham theorem, this calculation method relies not only on gyrodynamic similarity criteria, but also on functional dependences for the laws of distribution of cavitation bubbles according to various characteristics (specific size bubbles, the degree of opening of the node “separator-external locking shell”). This takes into account a wide range of design and operating parameters, including the required valve capacity, as well as the physical and mechanical characteristics of the working medium. A block diagram of the calculation of the node “separator-external locking shell” for the specified axial valve is proposed. The influence of a set of design parameters for the “separator-external locking shell” assembly from the rational ranges of their variation obtained using the proposed analytical calculation algorithm on the size of cavitation bubbles is investigated. It has been established that when using the latest results in comparison with the values of parameters from irrational ranges of change, there is a tendency to reduce the ensemble average value of the diameter of the cavitation bubble by 1.95 times, when switching to a mode from 20% of the degree of separation of the separator to 80% of the opening of the throttle holes, the nominal valve capacity increases by 10.7 times. The results obtained illustrate the possibility of preventing an increase in the intensity of formation of cavities in the flow part of the control device already at the initial stage of the occurrence of cavitation.